Oxford new syllabus Mathematics workbook 2 - Har, Dr Yeap Ban (Karachi : Oxford university press, 2018)
The Oxford New Syllabus Mathematics Workbook 2 (7th Edition) is a companion workbook to the Oxford New Syllabus Mathematics 2 (7th Edition) textbook. It is designed to provide students with additional practice and reinforcement of the mathematical concepts introduced in the main textbook. The workbook emphasizes problem-solving skills and helps students develop a deeper understanding of mathematics through hands-on exercises.
Keywords: Mathematics : Workbook